2011
DOI: 10.1088/0004-637x/743/1/54
|View full text |Cite
|
Sign up to set email alerts
|

Correlating the Interstellar Magnetic Field With Protostellar Jets and Its Sources

Abstract: This paper combines new CCD polarimetric data with previous information about protostellar objects in a search for correlations involving the interstellar magnetic field (ISMF). Specifically, we carried out an optical polarimetric study of a sample of 28 fields of 10 × 10 located in the neighborhood of protostellar jets and randomly spread over the Galaxy. The polarimetry of a large number of field stars is used to estimate both the average and dispersion of the ISMF direction in each region. The results of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 68 publications
(77 reference statements)
5
34
0
Order By: Relevance
“…There are many relatively small polarization vectors around the south-east corner and the south-west corner of the image, flowing from north-west to south-east. Reflecting this, the histogram of θ H for all sources has a peak fitted with a Gaussian function with a peak angle of 111 • ± 4 • (Figure 2), which is consistent with the optical polarimetry results (Targon et al 2011).…”
Section: Observationssupporting
confidence: 85%
See 1 more Smart Citation
“…There are many relatively small polarization vectors around the south-east corner and the south-west corner of the image, flowing from north-west to south-east. Reflecting this, the histogram of θ H for all sources has a peak fitted with a Gaussian function with a peak angle of 111 • ± 4 • (Figure 2), which is consistent with the optical polarimetry results (Targon et al 2011).…”
Section: Observationssupporting
confidence: 85%
“…In this study, we use the value provided by Yang et al (2017). Targon et al (2011) conducted optical (R C band) polarimetry around the BHR 71 core. The obtained polarization angle (measured from north to east) was 102 • , indicating that the direction of the global magnetic fields is roughly parallel to the elongation axis of BHR 71 (∼ 130 • , see Figure 1, showing the elongation of the opaque region of BHR 71).…”
Section: Introductionmentioning
confidence: 99%
“…whereas misalignment between the same has also been reported in several studies (e.g., Wolf et al 2003;Ménard and Duchéne 2004;Targon et al 2011;Krumholz et al 2013;. Based on MHD simulations, Matsumoto and Tomisaka (2004) and Matsumoto et al (2006) found that the alignment between the magnetic field direction and outflow direction depends on the strength of the magnetic field, i.e., stronger the magnetic field, better the alignment.…”
Section: Relative Orientation Between Various Quantities Of the Cloudsupporting
confidence: 62%
“…Some study shows a good alignment of globule's magnetic field with outflow axis (e.g., Cohen et al (1984); Vrba et al (1986); Jones & Amini (2003)), whereas misalignment of magnetic field direction and outflow axis have been also reported (e.g. Wolf et al (2003); Ménard & Duchéne (2004); Hull et al (2013); Targon et al (2011);Soam et al (2015)). Soam et al (2015) reported that in IRAM 04191, the outflow is oriented almost perpendicular (∼ 84…”
Section: Correlation Between Magnetic Field and Outflowsmentioning
confidence: 99%